Emerging roles of the long non-coding RNA NEAT1 in gynecologic cancers - Maryam Farzaneh (17788460) (2023)
Gynecologic cancers are a worldwide problem among women. Recently, molecular targeted therapy opened up an avenue for cancer diagnosis and treatment. Long non-coding RNAs (lncRNAs) are RNA molecules (> 200 nt) that are not translated into protein, and interact with DNA, RNA, and proteins. LncRNAs were found to play pivotal roles in cancer tumorigenesis and progression. Nuclear paraspeckle assembly transcript 1 (NEAT1) is a lncRNA that mediates cell proliferation, migration, and EMT in gynecologic cancers by targeting several miRNAs/mRNA axes. Therefore, NEAT1 may function as a potent biomarker for the prediction and treatment of breast, ovarian, cervical, and endometrial cancers. In this narrative review, we summarized various NEAT1-related signaling pathways that are critical in gynecologic cancers. Other Information Published in: Journal of Cell Communication and Signaling License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s12079-023-00746-x